Pertumbuhan Bibit Kelapa Sawit dengan Aplikasi Fungi Mikoriza Arbuskular dan Beberapa Dosis Pupuk Fosfat - Rio Palasta; Maria Viva Rini (Politeknik Negeri Lampung, 2017)
Farmer dependence on inorganic fertilizers drives the inclination of the fertilizer price which in turn influence the production cost. Therefore, it is necessary to find alternative way to reduce the consumption of inorganic fertilizers. This study aims to determine the most suitable arbuscular mycorrhiza fungi (AMF) for oil palm seedlings, determining the best dosage of phosphate fertilizer for the growth of oil palm seedlings, and determine whether the growth response of oil palm seedlings to AMF inoculation is influenced by the dosage of P fertilizer given. Research had been conducted in the greenhouse and Plantation Production Laboratory, Faculty of Agriculture, University of Lampung from June 2012 until August 2013. The treatment design used was a factorial design and the experimental design used was a completely randomized block design. The first factor was AMF treatment i.e. control, Entrophospora sp. mv 3 isolate, Glomus sp. mv 9 isolate, Glomus sp. mv 10 isolate, and Glomus sp. mv 15 isolate. The second factor was the dosage of P fertilizer i.e. 23,32 g, 15,66 g, and 11,66 g per plant. Each treatment was repeated 4 times. The results showed that Glomus sp. mv 15 isolate was the most suitable type of AMF for oil palm seedlings. All dosages of P fertilizer tested showed no growth effect on oil palm seedlings and the growth response of oil palm seedlings to inoculation of AMF was not affected by dosage of P fertilizer.Â Keywords: Entrophospora, Glomus, mycorrhiza, oil palm, phosphate